Review of reasoning methods in clinical decision support systems - Aleksovska-Stojkovska, Liljana; Loshkovska, Suzana (My University, 2010)
Reasoning is a crucial task performed by the inference engine of the clinical decision support systems, which combines medical knowledge with patient specific data and generates relevant decisions. There are different reasoning methods, suitable for different knowledge representations and application area. This paper reviews the most common methods and describes how they are used in real systems. Furthermore, it outlines the remaining weaknesses of the reasoning mechanisms and provides directions for future research and improvements.
Keywords: Clinical decision support systems, inference, inference engine, reasoning methods